Sagan af Guðrúnu Ketilsdóttur. - Guðný Hallgrímsdóttir, 1963- author.
1 online resource.
Keywords: "A Tale of a Fool? explores the life of Guðrún Ketilsdóttir, a peasant woman born in Iceland around 1759"--